Impact of Store Environment on Impulse Buying (A case of International Modern Trade Retailers in Karachi) (KASBIT Business Journal, 2018)
Retail landscape in Pakistan has evolved rapidly giving rise to contemporary shopping practices in the country. The evolution in industry has attracted investment from both international and national retail chains giving rise to stiff competition. Hence, wining on customers and market share heavily relied on providing unique customer experience by enhancing store environment. Therefore, heavy investments are laid in nurturing pleasant store environment uplifting customer satisfaction and loyalty in return that helps increase store profitability. Moreover, significance to customer value proposition, convenience and discounted pricing strategy remained core to retailing dynamics in the country. Hence, research purpose instilled in determining the impact store environment have in inducing impulse buying behavior of the shoppers in the international modern trade stores in Karachi. This study used survey questionnaire to tap the response of the shoppers to administer relationship between independent variables that include music, light, layout and employees which are also referred as the determinants of in-store environment with impulse buying behavior being dependent variable of the study. The statistical tools adopted involved multiple regression analysis that helped test the hypothesis and the outcomes retrieved depicts that independent variables include music and layout has significant positive impact on the impulsive buying patterns. The managerial implications of our research recommended that the decision makers of the stores need to spend and manage the in-store determinants in a very careful manner in order to retain and welcome maximum number of shoppers which eventually helps them to increase their sales volume and profitability.
Keywords: store environment; impulse buying behavior; music; light; layout and employee